2009
DOI: 10.1002/jgm.1376
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gene expression between sonoporation in tumor and in muscle

Abstract: The present study indicates that muscle tissue is a good target site for producing large amounts of gene products for the purpose of gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…1). Our results are in agreement with another recent report that demonstrated that muscle was more amenable to ultrasound-and nanobubble-mediated gene transfer than were subcutaneous or orthotropic tumors (32). In addition, we demonstrated that gene transfer mediated by ultrasound and nanobubbles can also be performed on mice with arthritis or muscle degeneration, suggesting that these pathologies do not impair the transduction potential of the methodology.…”
Section: Discussionsupporting
confidence: 93%
“…1). Our results are in agreement with another recent report that demonstrated that muscle was more amenable to ultrasound-and nanobubble-mediated gene transfer than were subcutaneous or orthotropic tumors (32). In addition, we demonstrated that gene transfer mediated by ultrasound and nanobubbles can also be performed on mice with arthritis or muscle degeneration, suggesting that these pathologies do not impair the transduction potential of the methodology.…”
Section: Discussionsupporting
confidence: 93%
“…Optison and SonoVue MB have been shown to mediate transfection of pLuc in muscle and tumor with similar efficiencies following sonoporation (Tsai et al, 2009). Our results suggest that although the exact equivalency in dosage between Ad and sonoporated plasmids is difficult to achieve, at the doses used (Pislaru et al, 2003;Passineau et al, 2010), our imaging data suggested that the sonoporation method can be about four times (in vivo) to *10 times (ex vivo) more efficient than Ad.…”
Section: Discussionmentioning
confidence: 45%
“…For example, sonoporation has been used to deliver reporter genes encoding B-galactosidase (Hauff et al, 2005), enhanced green fluorescent protein (Tsai et al, 2009), and luciferase (Aoi et al, 2008;Li et al, 2009). These sonoporation approaches are also being applied to cancer therapy.…”
Section: Discussionmentioning
confidence: 98%
“…However, the half-lives of the anti-angiogenic proteins in circulation are usually short (for example, in vivo decay of endostatin is bi-exponential, resulting in a half-life (t 1/2 ) of 42.3 min and a b t 1/2 of 12.9 h), 37 which may result in disappointing therapeutic effects when used in clinical treatment. 33 On the other hand, DNA delivered into the muscle can be retained in the tissue for up to 1 week, 26 thus enabling the production of anti-angiogenic proteins over a longer period of time. The expression can be further sustained with repeated US treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our previous study demonstrates that US-mediated gene delivery is more effective in muscle tissue than in tumors. 26 The goal of the current study is to test the therapeutic effect of US-mediated intramuscular expression of anti-angiogenic genes on distant orthotopic tumors. Our results show that repeated US administration to deliver endostatin (ED) or calreticulin (CRT) genes to muscle led to a significant antitumor effect on distant orthotopic tumors in the liver, brain or lungs.…”
Section: Introductionmentioning
confidence: 99%